The multiphasic profile of free fatty acids during the intravenous glucose tolerance test is unresponsive to exogenous insulin - Sumner, A.E.; Bergman, R.N.; Vega, G.L.; Genovese, D.J.; Cochran, C.S.; Pacak, K.; Watanabe, R.M.; Boston, R.C. (Metabolism, clinical and experimental, 2004)
As small increments in insulin concentration profoundly affect lipolysis, our goal was to describe the free fatty acid (FFA) profile during the frequently sampled intravenous glucose tolerance test (FSIGT) and determine if both endogenous and exogenous insulin influenced the FFA profile. Thirteen subjects had both a glucose-only (GO-FSIGT) and insulin-modified FSIGT (IM-FSIGT). Both protocols were of 6 hours duration. At baseline an intravenous glucose bolus (0.3 g/kg) was given. In the IM-FSIGT, insulin was infused from 20 to 25 minutes (4 mU/kg · min). Six additional subjects had both an IM-FSIGT and a normal saline study (NS-Study). For the NS-Study, normal saline solution was infused instead of glucose and insulin. Fasting glucose, insulin, FFA and epinephrine concentrations were similar for all tests. Endogenous insulin peaked at 4 ± 1 minute in both FSIGTs. The mean calculated peak time of exogenous insulin in the IM-FSIGT was 26 ± 1 minute. Glucose concentrations were lower and epinephrine concentrations higher in the IM-FSIGT versus GO-FSIGT. During the FSIGTs, the FFA time course revealed four distinct phases, which did not differ between protocols. In phase I (0 to 11 minutes), FFA levels remained near basal (491 ± 183 μmol/L); in phase II (11 to 79 minutes), FFA levels declined achieving a nadir of 139 ± 63 μmol/L; in phase III (79 to 188 minutes), FFA levels rose linearly and reattained basal levels; and in phase IV (188 to 360 minutes), FFA levels rose above basal and plateaued at 732 ± 214 μmol/L ( P < .001). In the NS-Study, FFA levels remained near baseline (388 ± 118 mEq/L) until 180 minutes and then trended upward to 618 ± 258 μmol/L at 360 minutes. FFA concentrations from 180 to 360 minutes did not differ in the IM-FSIGT versus NS-Study. As the 4 FFA phases did not differ between protocols, the insulin effect on FFA levels in the FSIGT can be attributed to endogenous insulin. But the similarity in FFA levels from 180 to 360 minutes in the IM-FSIGT and NS-Study suggests diurnal variation and not a dynamic related to insulin or the FSIGT protocol is responsible for the final suprabasal FFA plateau.